Legislative aspects and doctrinal opinions regarding legislative events - Boghirnea, Iulia (International Journal of Legal and Social Order, 2023)
Through this study, we want to bring back to attention the legislative events provided by law 24/2000, as a result of the appearance in their list of consolidation, which is regulated by law as not having legal effects. There is a similar legal institution in the Union legislation which has the value of republication in domestic law. That's why we have briefly analysed the legislative events provided by the law and the effects they have produced, comparing them to the new technical procedure called consolidation.